2019
DOI: 10.1128/aem.00234-19
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Sigma Factor RpoX Is a Part of the RpoE Regulon and Plays Distinct Roles in Stress Responses, Motility, Biofilm Formation, and Hemolytic Activities in the Marine Pathogen Vibrio alginolyticus

Abstract: Vibrio alginolyticus is one of the most abundant microorganisms in marine environments and is also an opportunistic pathogen mediating high-mortality vibriosis in marine animals. Alternative sigma factors play essential roles in bacterial pathogens in the adaptation to environmental changes during infection and the adaptation to various niches, but little is known about them for V. alginolyticus. Our previous investigation indicated that the transcript level of the gene rpoX significantly decreased in an RpoE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Similarly, during the stationary phase cells, the rpoH gene involved in growth and metabolism, which redirects transcription to hundreds of genes involved in multiple stress resistance, maintenance metabolism and other stationary phase functions ( Weber et al., 2005 ) and another study showed decreased the expression of stress related genes during heat stress ( Ferreira et al., 2013 ). High expression levels of rpoH and rpoS seem to be able to rescue the growth defects ( Gu et al., 2019 ). The decreased transcription of the stress response genes rpoS and rpoH proved that glucose is not cell-friendly for any tested strain.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, during the stationary phase cells, the rpoH gene involved in growth and metabolism, which redirects transcription to hundreds of genes involved in multiple stress resistance, maintenance metabolism and other stationary phase functions ( Weber et al., 2005 ) and another study showed decreased the expression of stress related genes during heat stress ( Ferreira et al., 2013 ). High expression levels of rpoH and rpoS seem to be able to rescue the growth defects ( Gu et al., 2019 ). The decreased transcription of the stress response genes rpoS and rpoH proved that glucose is not cell-friendly for any tested strain.…”
Section: Resultsmentioning
confidence: 99%
“…Motility in A. baumanni was also inversely correlated with hemolysis. Although the molecular mechanism by which this regulation occurs remains obscure, co-regulation of stress response, motility, biofilm formation, and hemolysis has been demonstrated in other bacterial pathogens, such as Vibrio alginolyticus [ 27 ]. In this pathogen, alternate sigma factor RpoX is implicated as a critical regulator of the expression of virulence factors associated with these important processes.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial biofilm formation is often closely related to motility. For example, RpoX plays distinct roles in stress response, motility, and biofilm formation in the marine pathogen Vibrio alginolyticus [63]. ToxR is required for the biofilm formation and motility of Vibrio parahaemolyticus [64].…”
Section: Discussionmentioning
confidence: 99%